2013
DOI: 10.1590/s0004-28032013000200025
|View full text |Cite
|
Sign up to set email alerts
|

INITIAL EXPERIENCE OF ENDOSCOPIC SUBMUCOSAL DISSECTION IN BRAZIL TO TREAT EARLY GASTRIC AND ESOPHAGHEAL CANCER: a multi-institutional analysis

Abstract: -Objective -This study aimed to evaluate the feasibility and clinicopathological characteristics of early gastric and esophageal cancers treated with endoscopic submucosal dissection (ESD) at five centers in Brazil. (range, 20-150 min). Complications included pneumomediastinum in two (12.5%) patients and stenosis in one (6.2%). Mean duration of follow-up was 8.6 months, with no local recurrence despite the presence of lateral margin compromise. Conclusion -Different centers in Brazil feasibly perform ESD with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…Long-term outcomes are rarely described. Nevertheless, all the authors have concluded that esophageal ESD is feasible, and rates of complete resection and complications were not significantly different from Eastern series [16,24,28,33,38,40]. For the stomach the scenario is similar.…”
Section: Appendix 3 Training In Endoscopic Submucosal Dissection !mentioning
confidence: 92%
See 1 more Smart Citation
“…Long-term outcomes are rarely described. Nevertheless, all the authors have concluded that esophageal ESD is feasible, and rates of complete resection and complications were not significantly different from Eastern series [16,24,28,33,38,40]. For the stomach the scenario is similar.…”
Section: Appendix 3 Training In Endoscopic Submucosal Dissection !mentioning
confidence: 92%
“…Inexperience in ESD might not only be associated with higher risk for procedure-related complications, but also with the risk of incomplete resection [219]. For these reasons ESD has been restricted to tertiary referral centers, although a multicenter retrospective questionnaire study showed that outcomes of ESD for early gastric neoplasms at low volume centers were as good as those at high volume centers [33,220]. Farhat et al reported that with increased endoscopist experience the duration of ESD diminished significantly for the same relative size of lesions.…”
Section: Appendix 3 Training In Endoscopic Submucosal Dissection !mentioning
confidence: 99%
“…From the oncological perspective it has been suggested that ESD techniques are equally effective in comparison to surgical treatment for superficial neoplasms with negligible risk of lymph node metastasis (2,3) . Moreover, ESD application has been expanded on a worldwide basis and is progressively attracting attention and acceptance (6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…As it was initially proposed, EMR consists of a minimally invasive technique used for diagnosis, staging and treatment of superficial tumors, including the sessile polyps of the gastrointestinal mucosa (7) . In contrast, ESD results in relatively large en bloc resections, allowing lower rates of local tumor recurrence and better pathological assessment (2,8) . Although these surgical procedures have emerged as important therapeutic modalities for superficial tumors of the gastrointestinal mucosa, they are not widespread yet, inasmuch as they are highly dependant on the endoscopist's expertise.…”
mentioning
confidence: 99%